Minimally invasive teeth whitening enhancements after orthodontic treatment with in-office bleaching: two case reports - Hikmah, Noor; Lestari, Dwi Puji; Hurint, Theresia Paskaedith Lodang; Natsir, Nurhayaty; Nugroho, Juni Jekti; Dwiandhany, Wahyuni Suci; Trilaksana, Aries Chandra; Rovani, Christine A (Conservative Dentistry Journal, 2024)
Background: Teeth discoloration is one of the adverse effects of orthodontic treatment which causes aesthetic issues that effect on a person’s appearance. The management of teeth discoloration can be done with bleaching because it is easier to perform, faster, more effective, and more conservative than other treatments such as crowns and veneers. There are two types of bleaching techniques supervised by dentists: home bleaching and in-office bleaching. In-office bleaching is one of the most conservative and non-invasive treatment options to restore the aesthetics of discolored teeth. Purpose: This case report observes management of tooth discoloration after orthodontic treatment with in office bleaching using hydrogen peroxide 40%. Case 1: A 24-year-old woman came to Universitas Hasanuddin Dental and Oral Hospital with complaints of yellowish upper and lower teeth after removal of her fixed orthodontic appliance. Case 2: A 24 years old woman came to Universitas Hasanuddin Dental and Oral Hospital with complaints of upper and lower front teeth appearing yellowish in color, noticed from 2 years ago and had undergone orthodontic treatment for four years. Case Management: From clinical examination, both patients’ teeth have no history of caries, sensitive tooth and gingival recession. The Teeth were sensitive to vitality test. The discoloration was treated with external bleaching using 40% hydrogen peroxide. Conclusion: External Bleaching using 40% hydrogen peroxide have results in significant discoloration without changing the shape and arrangement of the patient’s teeth